2010
DOI: 10.1111/j.1365-2044.2010.06424.x
|View full text |Cite
|
Sign up to set email alerts
|

National representation in the anaesthesia literature: a bibliometric analysis of highly cited anaesthesia journals*

Abstract: SummaryWhile previous studies have investigated the country of origin of anaesthetic publications, they have generally used a MEDLINE computer search to identify original articles and have often excluded non-English language articles. We undertook a hand-search of journals in the Journal Citation Reports Ò using the subject category of Anesthesiology. We quantified the number of original articles, editorials, review articles, case reports and correspondence attributed to each country. We also calculated the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
55
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 23 publications
6
55
0
1
Order By: Relevance
“…This ratio has been identified in many medical fields [9][10][11][12]. In our study, we found a slightly higher proportion for middle-income countries.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…This ratio has been identified in many medical fields [9][10][11][12]. In our study, we found a slightly higher proportion for middle-income countries.…”
Section: Discussionsupporting
confidence: 54%
“…Also, bibliometric analysis can be used to investigate trends in scholarly publications and the relative importance of articles on a specific topic. Bibliometric analysis has been used to determine national contributions to research fields including oncology [4], cardiovascular disease [5], rheumatology [6], nutrition and dietetics [7], diabetic retinopathy [8], emergency medicine [9], critical care medicine [10], anaesthesia [11], plastic and reconstructive surgery [12], foot and ankle research [13], and arthroscopy [14].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3 Despite the several existing international partnerships for anesthesia residency programs, there remains a paucity of literature to inform educators embarking on new programs. 4 The most extensively described initiatives are the Nepalese and Rwandan programs, both of which are affiliated with the Canadian Anesthesiology Society International Education Foundation. 2,[5][6][7][8][9][10][11] Nevertheless, there also exist relatively unpublicized North-South partnerships such as those in Malawi, Kenya, Ethiopia, Madagascar, and Uganda.…”
Section: Résumémentioning
confidence: 99%